2020
DOI: 10.1136/archdischild-2019-317990
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury following intravenous acyclovir in children

Abstract: ObjectiveThe objective of this study was to describe the incidence of acute kidney injury (AKI) in children receiving intravenous acyclovir and determine risk factors that may be associated with it.DesignThis was a retrospective cohort study, conducted by chart review.SettingThe study was conducted across two paediatric hospitals.PatientsAll inpatients that received intravenous acyclovir in records from January 2015 to December 2015 were reviewed. Only patients with creatinine measurements taken before and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Eighteen children (21.7%) had new-onset AKI during hospital stay, none requiring RRT. These findings were similar to that reported by Sandery et al (22), where 12 of 27 patients (44%) who developed AKI remained in stage 1 at their last creatinine measurement (23). Nephrotoxicity associated with IV acyclovir is common and necessitates monitoring of renal function (12–14).…”
Section: Discussionsupporting
confidence: 92%
“…Eighteen children (21.7%) had new-onset AKI during hospital stay, none requiring RRT. These findings were similar to that reported by Sandery et al (22), where 12 of 27 patients (44%) who developed AKI remained in stage 1 at their last creatinine measurement (23). Nephrotoxicity associated with IV acyclovir is common and necessitates monitoring of renal function (12–14).…”
Section: Discussionsupporting
confidence: 92%
“…Hyperfiltration state may indicate kidneys have little reserve capacity, thus intolerable to nephrotoxic insults and prone to incidence of AKI. Sandery et al also demonstrated in their study that the elevated baseline eGFR was a significant risk factor of AKI in children receiving nephrotoxic drugs, and attributed the pathogenesis to GH [27].…”
Section: Discussionmentioning
confidence: 90%
“…4143 There was also increasing evidence for the nephrotoxicity associated with nucleoside analogs such as acyclovir and ganciclovir. 4447 Our study showed that foscarnet was associated a significantly lower risk of hospital-acquired AKI compared with acyclovir.…”
Section: Discussionmentioning
confidence: 70%